First record and a new species of Metopiasoides Comellini (Coleoptera, Staphylinidae, Pselaphinae) from Peru - Asenjo, Angélico (Zootaxa, 2016)
Metopiasoides jefersoni Asenjo, a new species, of the Neotropical pselaphine tribe Metopiasini, is described from Urubamba Valley in southeastern Peru (Cusco state). Major diagnostic features are illustrated.